Síntesis de aciltiouretanos de potencial aplicación hidrometalúrgica a partir de ácidos aromáticos y compuestos hidroxilados - Ascoy García, Dalia Ynés (2005)
This research work deals with the synthesis of acylthiourethanes from carboxylic acids and hydroxyl compounds and their transformation their copper (II) complexes. As starting acids were used benzoic, isophthalic and terephthalic acids. As hydroxyl compounds were utilized methyl, ethyl, n-propyl, isopropyl, isobutyl and benzyl alcohols, as well as ethylene glycol, phenol, p-nitrophenol and hydroquinone. The synthetic route implies the successive transformation the aromatic acids in their acyl chlorides and acylisotiocyanates. The acylthiourethanes were obtained in yields ranging from 75 to 3 %, by nucleophilic attack of the hydroxyl compounds over the acylisothiocyanates. Copper (II) complexes were prepared from the acylthiourethanes by reaction with copper (II) acetate. The products structural characterization was performed by their melting points, solubilities, thin layer chromatography and infrared spectroscopy